Rivalry and bargaining between governmental and private kindergarteners (Journal Of Educational and Psychological Researches, 2017)
The study aims to identify the bargaining differences between the governmental and private kindergarteners; the rivalry differences between the governmental and private kindergarteners; the rivalry and bargaining differences among private kindergarteners; and the rivalry and bargaining differences among governmental kindergarteners. The researchers had raised a question; is there any difference of rivalry and bargaining between governmental and private kindergarteners?. A total of (150) kindergarteners ranged from 5 to 6 years old, (90) student from governmental kindergarten and (60) student from private kindergarten, were selected as a sample of this study. Fifteen governmental and private kindergarten were chosen from al-rasafa directorates’ (first, second, and third). The researchers constructed two scale, one to measure the rivalry between governmental and private kindergarteners and the other to measure the bargaining between governmental and private kindergarteners. Reliability and validity were tested. The results had revealed that bargaining among governmental kindergarteners higher than private ones, on the other side, rivalry among private kindergarteners higher than governmental ones. Rivalry showed more significance when it came to compare with bargaining among private kindergarteners.Bargaining revealed more significance when it came to compare with rivalry among governmental kindergarteners.